Pengaruh Rendam Kaki Dengan Air Hangat Terhadap Pemenuhan Kebutuhan Tidur Lansia Di Yayasan Persaudaraan Kristen Damai Lembaga Kesejahteraan Sosial Lanjut Usia di Ronomuut Kota Manado - Ditia Puili; Kristine Dareda; Nurlela Hi Baco (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Sleep is an altered state of consciousness when an individual's perception and reaction to the environment decreases. Sleep disorders often occur in the elderly, decreased sleep quality. Bathing therapy with warm water can cause blood vessels, where the warm water makes blood circulation smooth and creates a feeling of relaxation, thereby improving the quality of sleep. The aim of this research to identify the effect of iveness soaking feet therapy with warm water on meeting sleep quality in the elderly at the Peace Christian Brotherhood Foundation, Social Welfare Institution for the Elderly in Ranomuut, Manado City. This research method use One Group Pre Test – Post Test Design approach. The population in the study was 15 using using a total sampling technique, the research used a questionnaire sheet and SOP 0.05. The results of research using the paired T test obtained a P value (0.000) where p value ≤ a=(0.05) which means there is an effect of soaking foat with warm water on meeting sleep qualityesin the elderly. The conclusion in this research there is an effect iveness of soaking feet in warm water on meeting sleep qualikes in the elderly. At the Peaceful Christian Brotherhood Foundation, Social Welfare Institution for the Ederly in Ranomuut, Manado City. It is recommended that the results of this research provide knowledge to the public about soaking feet in warm water.